Implementation of Innovative Learning Models in Chemistry Lessons During the Covid-19 Pandemic - Fransiskus Gultom; Hernawaty Hernawaty; Poniyah Simanullang (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to increase students' activeness and learning outcomes in Chemistry. It can be useful in providing an interesting and not boring learning experience for students, through blended learning, students are directly involved in learning activities, to increase student chemistry learning activity during the Covid-19 pandemic. This research is classroom action research consisting of two cycles, each consisting of four activities: planning, action, observation, and reflection. Learning activities with this blended learning model will continue to the next cycle if the indicators of success have not been achieved. The sample in this study was 32 students of class XI MIPA Jambi Medan Private High School. The study’s results used a blended learning model during the Covid-19 pandemic. From the results of research and discussion that have been obtained, several conclusions can be drawn, including; In cycle I, the number of students who are in the active category is 46.88% and the very active is 9.38%, so the number of student activities is 56.26%; In cycle II there was an increase in the activity category by 37.50% and students who were very active increased by 50.00%, so that the number of student activities was obtained by 87.50%, and student learning outcomes increased with the achievement of the minimum completeness criterion score in the first cycle of 64% and in the second cycle it is obtained by 76.00%. So that the number of students' learning completeness is obtained by 84.21%.